Characterisation of the Eulerian and Lagrangian accelerations in the intermediate field of turbulent circular jets. Issue 1 (2nd January 2017) - Kim, J.-T.; Liberzon, A.; Chamorro, L. P.
ABSTRACT: A rich data-set of Lagrangian trajectories from 3D particle tracking velocimetry is used to study the structure of various acceleration components, vorticity, and strain in the intermediate field of a circular jet at Reynolds number Re = 6000. The total acceleration is decomposed into three distinctive sets: (1) streamwise–radial; (2) tangential–normal; and (3) local–convective components. Probability density function (PDF) and joint distributions of each set are characterised at various radial locations from the jet core within a streamwise band 16 ≤ x / d h ≤ 17, where d h is the diameter of the pipe. The PDF of the relative angle between the acceleration components and the velocity vector is also included to aid the characterisation. Results show that the acceleration components are described by two distinctive distributions: one of them exhibits symmetry and heavy tails, while the other is best fitted by a power-law type. The tails of acceleration PDFs are heavier with larger radial distance from the core. The increased departure from the Gaussian distribution with the distance from the core is a result of the increasing turbulence levels promoted by the mean shear. The variation of the third and fourth moments between the streamwise–tangential and the radial–normal accelerations indicate the anisotropy of the jet. Joint PDF of each acceleration decomposition exhibits distinctive distribution that appears to depend from the distance from the jet core. However, the vorticity and strain show similar PDF across radial distances. Finally, complementary analysis of a jet from a semicircular pipe shows the footprint of the nozzle geometry in the acceleration structure of jets.